Slagging behavior modeling in coal gasifiers using two-way coupled slag model with CFD. (1st December 2020) - Ge, Jin; Wang, Zhihua; Wan, Kaidi; He, Yong; Zhou, Zhijun; Huang, Zhenyu
Abstract: In pulverized-coal gasifiers, wall slagging behavior is an important issue associated with ash handling and discharge. Numerical methods have been widely employed to predict the slag flow and heat transfer on the gasifier wall. However, most of the analytical models are only one-way coupled with the simulation of the gasification reactor. In the present study, the slag model was integrated into a commercial computational fluid dynamics (CFD) solver to achieve two-way coupling. The coupled mass, momentum and energy equations were solved iteratively until convergence. The simulations of a simplified gasifier show that the solid slag thickness was seriously affected by the heat flux from gas to slag surface. The proposed two-way coupled slag model was able to give more reasonable predictions compared with other offline slag models since the heat transfer between the gas and the slag could be modeled more accurately. Through analyzing the energy balance in the slag layer, it is found that most of the heat flux from gas was extracted by the cooling water. However, the effect of the heat flux absorbed by the flowing liquid slag became important under high gas temperatures and ash deposition rates.